Electromagnetic Field as a Treatment for Cerebral Ischemic Stroke - Moya Gómez, Amanda; Font, Lena Pérez; Brône, Bert; Bronckaers, Annelies (Frontiers in Molecular Biosciences, 2021)
Cerebral stroke is a leading cause of death and adult-acquired disability worldwide. To this date, treatment options are limited; hence, the search for new therapeutic approaches continues. Electromagnetic fields (EMFs) affect a wide variety of biological processes and accumulating evidence shows their potential as a treatment for ischemic stroke. Based on their characteristics, they can be divided in stationary, pulsed and sinusoidal EMF. The aim of this review is to provide an extensive literature overview ranging from in vitro to even clinical studies within the field of ischemic stroke of all EMF-types. A thorough comparison between EMF-types and their effects is provided, as well as on overview on the signal pathways activated in cell types relevant for ischemic stroke such as neurons, microglia, astrocytes and endothelial cells. We also discuss which steps have to be taken to improve their therapeutic efficacy in the frame of the clinical translation of this promising therapy.